AN ENVIRONMENTAL AUDIT OF FINANCIAL-ECONOMIC ACTIVITY OF THE ENTERPRISE (Journal of Economic Research & Business Administration, 2018)
The article is devoted to the environmental audit as a form of financial control (supervision). For Kazakhstan the very urgent task is the development of this form of financial supervision as an environmental audit of ecological and economic activities of enterprises. It becomes an important tool to ensure environmental security and sustainable development of enterprises.The article substantiates the necessity of using environmental auditing in the financial-economic activity of enterprises. Reveals foreign experience of application of the environmental auditing procedure and the specificities of its development in Kazakhstan. Compares the financial and environmental audit, showing goals, objectives and types of environmental audit in relation to the Kazakhstan enterprises. It is noted that in many respects the problems of the implementation procedure of environmental audit in the financial-economic activity of enterprises and organizations related to the lack of a full understanding of the adverse ecological situation in Kazakhstan and the world, lack of experience with this type of activity, imperfect regulatory framework.The article also considers the question of environmental audits in financial economic activity of the enterprise. Environmental auditing can be useful to establish additional measures for the study of risks and security and the timely introduction of sustainable means of risk prevention